2021
DOI: 10.3892/ol.2021.13000
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of microfibrillar‑associated protein 2 is closely associated with tumor angiogenesis and poor prognosis in hepatocellular carcinoma

Abstract: Abnormal expression of microfibrillar-associated protein 2 (MFAP2), a key regulator of cellular differentiation, affects the occurrence and progression of tumors. However, the underlying role of MAFP2 in hepatocellular carcinoma (HCC) remains unclear. In the present study, patterns of MFAP2 expression in HCC were analyzed using sequencing data from The Cancer Genome Atlas database. Expression profiles of MFAP2, as well as those of epithelial-mesenchymal transition (EMT)-related proteins, were compared between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 31 publications
2
7
0
Order By: Relevance
“…Next, we explored MFAP2 expression in various types of glioma and observed that MFAP2 expression levels correlated positively with tumor grade, histology, recurrence, and other biomarkers such as 1p19q codeletion, IDH status, TERT expression, ATRX status, and chromosomes 7 and 10. These outcomes correspond with a former report that MFAP2 promotes epithelial-mesenchymal transformation, proliferation, and migration in tumor cells ( Chen et al, 2020 ; Yao et al, 2020 ; Zhang et al, 2021 ). The results of the functional analysis of MFAP2 protein in glioma revealed that MFAP2 correlated with signaling pathways activated in gliomas, such as activation of matrix metalloproteinases, MET promotion of cell motility, chemokine receptor binding to chemokines and cell cycle checkpoints.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Next, we explored MFAP2 expression in various types of glioma and observed that MFAP2 expression levels correlated positively with tumor grade, histology, recurrence, and other biomarkers such as 1p19q codeletion, IDH status, TERT expression, ATRX status, and chromosomes 7 and 10. These outcomes correspond with a former report that MFAP2 promotes epithelial-mesenchymal transformation, proliferation, and migration in tumor cells ( Chen et al, 2020 ; Yao et al, 2020 ; Zhang et al, 2021 ). The results of the functional analysis of MFAP2 protein in glioma revealed that MFAP2 correlated with signaling pathways activated in gliomas, such as activation of matrix metalloproteinases, MET promotion of cell motility, chemokine receptor binding to chemokines and cell cycle checkpoints.…”
Section: Discussionsupporting
confidence: 92%
“…MFAP2 was recently reported to be associated with various malignant tumors. For example, as a prognostic marker of hepatocellular carcinoma, MFAP2 leads to hepatocellular carcinoma cell epithelial-mesenchymal transition, and also promotes hepatocellular carcinoma angiogenesis via vascular endothelial growth factor A ( Zhang et al, 2021 ); MFAP2, an oncogene in gastric cancer, promotes the progression of cancer through the integrin α5β1/FAK/ERK1/2 signaling pathway ( Yao et al, 2020 ); MFAP2 is highly expressed in melanoma and leads to melanoma invasion and migration by upregulating EMT-related proteins and Wnt/β-catenin signal pathway ( Chen et al, 2020 ). However, the expression and effection of MFAP2 on gliomas have yet to be reported.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that MFAP2 plays an important role in lung cancer, consistent with the results of previous studies [9,12,15]. MFAP2 has been correlated with angiogenesis and prognosis in HCC [16]. In addition, MFAP2 is a diagnostic and prognostic biomarker of papillary thyroid cancer (PTC) [9] and can potentiate the motility of melanomas [12].…”
Section: Discussionsupporting
confidence: 89%
“…For example, hepatocellular carcinoma cell migration and invasion ability were reduced by inhibiting EMTrelated protein expression in MHCC97H cells after MFAP2knockdown. Furthermore, MFAP2 inhibition by si-MFAP2 in YY-8103 and HuH-7 cells showed time-dependent low relative mobility (20,21). In vitro colorectal adenocarcinoma studies found that MFAP2 silencing inhibited the migration of SW480 and HCT116 cells (19).…”
Section: Mfap2 Is Involved In Tumor Cell Invasion and Metastasismentioning
confidence: 99%